1992
DOI: 10.1007/bf01296001
|View full text |Cite
|
Sign up to set email alerts
|

Role of capsaicin-sensitive afferent neurons in mucosal blood flow response of rat stomach induced by mild irritants

Abstract: The role of capsaicin-sensitive sensory nerves in gastric mucosal blood flow (GMBF) responses to mild irritants was investigated in the rat stomach mounted on a lucite chamber using hypertonic NaCl and 0.2 N HCl. Exposure of the mucosa to hypertonic NaCl (0.5, 0.75, 1 M) for 10 min caused a reduction in the transmucosal potential difference (PD) in a concentration-related manner, followed by an increase of luminal pH and GMBF. In contrast, mucosal application of 0.2 N HCl caused no or little change in PD and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 25 publications
3
37
0
Order By: Relevance
“…It has been shown that such GMBF responses in the stomach after damage are mediated by capsaicin-sensitive neurons as well as endogenous prostaglandins (PGs) (22). We confirmed that the increase in GMBF caused by TC was significantly reduced in capsaicin-pretreated rats.…”
Section: Discussionsupporting
confidence: 76%
“…It has been shown that such GMBF responses in the stomach after damage are mediated by capsaicin-sensitive neurons as well as endogenous prostaglandins (PGs) (22). We confirmed that the increase in GMBF caused by TC was significantly reduced in capsaicin-pretreated rats.…”
Section: Discussionsupporting
confidence: 76%
“…The increase of luminal pH in the stomach exposed to mild irritants is considered to be due to both inhibition of acid secretion and diffusion of HC03 (17), while the GMBF response may be mediated by endogenous PGs and capsaicin-sensitive sensory neu rons (11,18). To our surprise, the increase of luminal pH after exposure to L-arginine was markedly inhibited by the NO biosynthesis inhibitor L-NAME, despite the fact that other parameters remained unaffected.…”
Section: Discussionmentioning
confidence: 57%
“…Although gastric hyperemia is not the exclusive mechanism of gastric cytoprotection as induced by PGE 2 or capsaicin-sensitive afferent neurons (Stroff et al, 1996;Araki et al, 2000), GMBF is considered to be a factor in capsaicin-induced gastric protection under certain experimental conditions (Holzer et al, 1991;Takeuchi et al, 1993). We previously reported that the gastric hyperemic response to capsaicin was also significantly mitigated by indomethacin, suggesting an involvement of endogenous PGs in this action (Matsumoto et al, 1992). In the present study, we confirmed that intragastric capsaicin caused a marked increase of GMBF in wildtype mice, in an indomethacin-sensitive manner.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that intragastric capsaicin increases GMBF in the rat stomach, and this effect is attenuated by sensory deafferentation after capsaicin pretreatment (Holzer et al, 1991;Matsumoto et al, 1992;Brzozowski et al, 1993). Although gastric hyperemia is not the exclusive mechanism of gastric cytoprotection as induced by PGE 2 or capsaicin-sensitive afferent neurons (Stroff et al, 1996;Araki et al, 2000), GMBF is considered to be a factor in capsaicin-induced gastric protection under certain experimental conditions (Holzer et al, 1991;Takeuchi et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation